Geographic based maximum lifetime routing in data aggregated wireless sensor networks with multiple base stations - TANG Wei; GUO Wei (Tongxin xuebao)
Network lifetime maximization in data-aggregated wireless sensor networks with multiple base stations by using geographic routing scheme was studied.To reduce the transmission overhead and avoid routing loops,home base station set potential descendent（HBSPD） algorithm was proposed,and linear programming method was used to optimize the network lifetime.Geographic location based multiple base station tessellation（GLMBST） algorithm was presented,and subgradient method was adopted to design the distributed algorithm.Performances of the proposed algorithms were verified by simulation experiments.